Evaluating biological properties of topsoil for post‐mining ecological restoration: different assessment methods give different results. (3rd July 2022) - D'Agui, Haylee M.; van der Heyde, Mieke E.; Nevill, Paul G.; Mousavi‐Derazmahalleh, Mahsa; Dixon, Kingsley W.; Moreira‐Grez, Benjamin; Valliere, Justin M.
Abstract : Salvaged native topsoil is a scarce, highly valuable resource in post‐mining restoration, being the main source of organic matter and nutrients and a major repository of plant propagules and soil microbes. During the mining process, topsoil is often stockpiled, and factors such as stockpile depth, season of stripping, and storage time can adversely affect topsoil functionality. We aimed to determine if soil functionality differs between undisturbed native reference topsoils and stockpiled topsoils of various age and origin, and whether measures of soil microbial community composition, soil respiration, and plant growth provide comparable assessments of soil functionality. We investigated this using select biological assessments of undisturbed native reference topsoils and stockpiled topsoils collected from seven mine sites representing a range of climate, soil, commodity, and vegetation types across the major mining province of Western Australia. Biotic properties of stored topsoil were idiosyncratic and variable across mine sites, and results differed based on the biotic measure being assessed. Biomass was generally lower for plants grown in stockpiled topsoils than for plants grown in native reference topsoils across mine sites. However, no single biotic measure provided an accurate assessment of soil functionality as reflected in plant growth responses. Overall, stockpiling adversely affected soil functionality and further research is needed to improve topsoil management procedures that may be site‐ and biome‐specific.